Autoinuminous necrotizing myositis: Case report and literature review - Cabrera Taipe, Victor Andres (2023)
Introduction: autoimmune necrotizing myositis is a rare disease in our environment, but it constitutes one of the forms of autoimmune inflammatory myopathies in approximately 20% of cases. Case report: This paper presents the case of a patient who was hospitalized in the internal medicine service who had a favorable outcome after his diagnosis. Conclusion: Autoimmune necrotizing myositis is an inflammatory myopathy that is difficult to diagnose, but is increasingly prevalent among myopathies.